Correlations between ultraviolet coloration, overwinter survival and offspring sex ratio in the blue tit. - Griffith, S; Ornborg, J; Russell, A; Andersson, S; Sheldon, B (2003)
We studied the correlations between offspring sex ratio, UV coloration and overwinter survival in a population of blue tits, breeding in Gotland, Sweden, over three consecutive breeding seasons. In 2 of 3 years, we found that females paired to males with relatively brighter UV-coloration produced a greater proportion of sons in their broods, and that this effect was significant with all 3 years combined, despite a significant year by male UV interaction. In addition, we found other correlates of sex ratio (breeding time, female age and clutch size) in some, but not all years, and some of these showed significantly different relationships with sex ratio between years. In both years for which data were available, there were indications that males with relatively brighter UV coloration, and that paired with females that produced male-biased clutches, were more likely to survive to the next year. In addition, we also found that in both males and females, individuals produced similar sex ratios in consecutive years. Because correlations with the sex ratio may be expected to be weak, variation in results between years within the same population may be explained by low statistical power or genuine biological differences. Our results suggest that conclusions about sex ratio variation in birds should be based on multiple years. The correlations that we found in some years of this study are consistent with models of adaptive sex ratio adjustment in response to mate quality. However, careful experimental work is required to provide tests of the assumptions of these models, and should be a priority for future work.